Biometric E-Voting With Multi Factor Authentication Using Iot Technology - et.al, Mr. M. Ganesan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India, which is one of the world's largest democracies, honest election methods are beset by problems such as booth capturing, rigging, pretend preference, and tampering with Electronic Voting Machines (EVMs), among others. The voting system is electronic, which removes the use of ballot paper to cast votes in elections because it is extremely time consuming and prone to errors. would possibly hit the system unknowingly or accidentally. The most downside in those methods is that the voter’s identity is victimized and additionally the count of non-voters will increase. Our main objective is to create a biometric e-voting system which is necessary to overcome the problems and difficulties of the normal voting methods such as EVM (Electronic Voting Machine) and traditional voting system. The proposed method of voting uses the voter's biometrics (fingerprint) and a physical key (RFID) to cast the ballot, as well as the ability to capture the voter's picture during the voting process. The voting information, including voting time and date, is securely stored on the server, and the voting results can be published instantly using this process.